2020
DOI: 10.1038/s41598-020-65054-5
|View full text |Cite
|
Sign up to set email alerts
|

EHD2 is a Predictive Biomarker of Chemotherapy Efficacy in Triple Negative Breast Carcinoma

Abstract: EHD2 is a mechanotransducing ATPase localized in caveolae invaginations at the plasma membrane. EHD2 has recently been associated with several human cancers, however the significance of EHD2 transcript levels in cancer prognosis remains debated. Breast cancer is the most commonly occurring cancer in women and prognosis is variable depending on the subtypes. Triple negative breast cancer (TNBC) often has a poor therapeutic response. The aim of this study was to assess the prognostic significance of EHD2 transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
(47 reference statements)
0
8
3
Order By: Relevance
“…1D ). Thus, our results indicate that high cytoplasmic EHD2 expression, a localization similar to that observed in normal mammary epithelium and BC cell lines, is a marker of more aggressive BC, contrary to published reports that did not assess the cytoplasmic/nuclear distribution of EHD2 and suggested its potential tumor suppressor role (11, 16, 22).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…1D ). Thus, our results indicate that high cytoplasmic EHD2 expression, a localization similar to that observed in normal mammary epithelium and BC cell lines, is a marker of more aggressive BC, contrary to published reports that did not assess the cytoplasmic/nuclear distribution of EHD2 and suggested its potential tumor suppressor role (11, 16, 22).…”
Section: Resultscontrasting
confidence: 99%
“…Our results differ from reports that reduction in EHD2 expression correlates with tumor progression in BC (11,22). Notably, a recent study, while it reported the depletion of EHD2 to an increase the oncogenic traits of BC cell lines in vitro, found low EHD2 expression in breast tumors to specify good prognosis and better chemotherapy response (16). Several factors could account for the discordance, including the lack of antibody validation of antibodies in prior studies, the high EHD2 expression in normal mammary adipocytes (Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that EHD2 may serve as a prognostic marker in breast cancer, papillary thyroid carcinoma, esophageal squamous cell carcinoma, and CRC ( 15 , 17 , 21 , 22 ). Furthermore, Shen et al reported that low EHD2 levels were associated with enhanced proliferation, migration, and invasion of triple negative breast cancer (TNBC) cells, and good prognosis in the highly proliferative TNBC subtype ( 23 ). In line with previous studies, we found that EHD2 was down regulated in LUAD tissues and correlated with poor prognosis through comprehensive bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%